Penerapan Model Pembelajaran Tipe Think Pair Share dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pkn Kelas V SD Negeri 15 Pekanbaru - Fitri Rahmadani; Deprizon Deprizon; Radhiyatul Fithri (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Whether or not an education in a country is successful is one of the learning models. One of the problems faced in learning Civics is the low learning outcomes of students. The use of conventional learning models causes students to be passive and have difficulty in understanding learning. The purpose of this study is to improve student learning outcomes, one of the efforts that can be made to improve student learning outcomes is to use the Think Pair Share (TPS) type cooperative learning model in the learning process. The research method used in this research is Descriptive Quantitative with a Classroom Action Research (PTK) approach which was carried out in 2 cycles. The results of the research obtained in cycle I of the material on the relationship between the Pancasila principles in Civics subjects by using the Think Pair Share type cooperative learning model achieved classical completeness of 50% and increased to % in cycle II. The results obtained in this study indicate that the Think Pair Share (TPS) learning model can improve the learning outcomes of Civics class V odd semester students of SD Negeri 15 Pekanbaru.